2013
DOI: 10.1007/s00228-013-1596-3
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic effects of regulatory nuclear receptors (PXR, CAR, RXRα and HNF4α) on docetaxel disposition in Chinese nasopharyngeal cancer patients

Abstract: The present exploratory study identified several SNPs in the genes encoding regulatory nuclear receptors which may account for the interpatient variability in docetaxel pharmacokinetics and pharmacodynamics. These findings highlight the important role of regulatory nuclear receptors on the disposition of docetaxel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…ERCC2 ( ERCC Excision Repair 2 ), a gene involved in repair of DNA damage, was demonstrated to be associated with docetaxel‐induced neutropenia . However, current researches on myelosuppression in Chinese Han population were limited to CYP3A4 , CYP3A5 , ACBC1 and nuclear receptors genes in docetaxel pathway . Therefore, a systematic study with more candidate genes that include additional drug transporter and metabolism genes is useful for probing the underlying mechanism of myelosuppression further.…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…ERCC2 ( ERCC Excision Repair 2 ), a gene involved in repair of DNA damage, was demonstrated to be associated with docetaxel‐induced neutropenia . However, current researches on myelosuppression in Chinese Han population were limited to CYP3A4 , CYP3A5 , ACBC1 and nuclear receptors genes in docetaxel pathway . Therefore, a systematic study with more candidate genes that include additional drug transporter and metabolism genes is useful for probing the underlying mechanism of myelosuppression further.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Several single‐nucleotide polymorphisms (SNPs) in relevant genes mentioned above have been associated with docetaxel myelosuppression . However, a number of studies have reported contradictory results that raise questions about the reliability of these biomarkers of docetaxel‐induced ADRs in different patient samples .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Moreover, endogenous compounds, such as steroid hormones and bile acids, can activate NR1I3 and NR1I2 involved also in various processes, such as cell differentiation and tumorigenesis as well as endocrine homeostasis. 20 In an exploratory study on the influence of regulatory nuclear receptors (NR1I2/pregnane X receptor, NR1I3/CAR, RXRα, and Hepatocyte Nuclear Factor 4 Alpha) on docetaxel pharmacokinetics in Chinese patients with nasopharyngeal cancer, Chew et al 21 identified several genetic variants in NR1I3 potentially related to hematologic toxicity. Furthermore, it has been found that nuclear receptors influenced the regulation at transcriptional level of ADME genes encoding phase I and II and drug transporters, after the activation by ligand binding.…”
Section: Discussionmentioning
confidence: 99%
“…While some PXR polymorphisms did not seem to interact with cancer growth, progression, or drug response (Justenhoven et al, 2011; Martino et al, 2013; Tham et al, 2007), several others were found to be significantly associated with cancer risk, growth, progression, or therapeutic outcome. For instance, the PXR polymorphisms have been shown to be associated with increased lung cancer risk in smokers (Zhang et al, 2014a) (Zhang et al, 2014b), higher prostate-specific antigen levels in prostate cancer patients (Reyes-Hernandez et al, 2014), lymphoma risk (Campa et al, 2012), pharmacokinetics and pharmacodynamics of docetaxel and doxorubicin in breast cancer patients, pharmacokinetics and toxicity of irinotecan in colorectal cancer patients (Mbatchi et al, 2016), risk of colorectal cancer (Andersen et al, 2010), Barrett’s esophagus and esophageal adenocarcinoma (van de Winkel et al, 2011a), and docetaxel disposition in nasopharyngeal cancer patients (Chew et al, 2014). Hence, a complete mapping of PXR polymorphisms is required to fully understand the PXR activation in a variety of tumors.…”
Section: Future Directionsmentioning
confidence: 99%